2014
DOI: 10.1177/0022022114535485
|View full text |Cite
|
Sign up to set email alerts
|

Development of Cultural Perspectives on Verbal Deception in Competitive Contexts

Abstract: Verbal deception may be considered morally reprehensible or acceptable depending on culturally relevant contextual factors and ethical perspectives. In the current study, Euro-Canadian (n = 180) and Han Chinese (n = 180) children ages 8 to 16 were recruited to investigate their moral evaluations of lying and truth-telling in competitive situations. The participants classified a story character’s statement told to either harm or help themselves or collectives of various group sizes (i.e., their class, school, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…Dmytro et al . () showed that children's evaluation of altruistic lies was positively related to the size of the group that would benefit from the lie. Hence, in the present study, the polite lies may not appear to be as good as the altruistic lies because the lie recipient receives less actual benefit, in that only some intangible feelings are saved at no cost on the liar's part.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dmytro et al . () showed that children's evaluation of altruistic lies was positively related to the size of the group that would benefit from the lie. Hence, in the present study, the polite lies may not appear to be as good as the altruistic lies because the lie recipient receives less actual benefit, in that only some intangible feelings are saved at no cost on the liar's part.…”
Section: Discussionmentioning
confidence: 99%
“…The difference has been explained in terms of an emphasis on social harmony and interdependence in the collectivist Chinese culture (Fu et al ., ; Kim, Kam, Sharkey, & Singelis, ; Wang, Bernas, & Eberhard, ). Hence, lying for the collective good is also evaluated positively by Chinese children (Dmytro et al ., ; Fu, Evans, Wang, & Lee, ; Fu, Xu, Cameron, Heyman, & Lee, ). Our current results therefore raise an interesting question: If concepts such as modesty and collective benefit are factored into liar motive, would the lie then become more ‘resistant’ to the label effect, especially in collectivist cultures?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, cultural groups influence children's perceptions of honesty, presumably through socialization agents such as parents. A topic within the literature on lie‐telling that is relevant to the group participation domain is differences in perceptions of honesty between collectivistic and individualistic cultures (Dmytro et al, 2014; Fu, Xu, Cameron, Heyman, & Lee, 2007; Lee, Xu, Fu, Cameron, & Chen, 2001; Lo, Fu, Lee, & Cameron, 2020). Generally, these studies have demonstrated that, although all children define truths and lies similarly, how they evaluate the morality of truths and lies and what factors they consider when doing so differs across cultures.…”
Section: The Domains‐of‐socialization Frameworkmentioning
confidence: 99%
“…The IDV dimension provides a measure of the degree to which people in a society are integrated into groups, with values such as autonomy and privacy held in higher regard among individualistic societies and values such as social harmony and loyalty valued more highly in collectivistic societies (Allik & Realo, 2004;Bochner, 1994;Hofstede, 1984Hofstede, , 2011 . The individualism versus collectivism contrast has been particularly influential in shaping cross-cultural work in developmental psychology (Chiu Loke et al, 2014;Dmytro et al, 2014;Greenfield et al, 2003;Krassner et al, 2016) . For instance, researchers have used the IDV dimension to explain why modesty behaviors vary across societies.…”
Section: On the Use Of Population-level Descriptors In Cross-societalmentioning
confidence: 99%